Answer:
x = 4(y + 6)/5
Step-by-step explanation:
2x - y = (3/4)x + 6
2x - (3/4)x = y + 6
(8x - 3x)/4 = y + 6
5x/4 = y + 6
5x = 4(y + 6)
5x = 4y + 24
x = (4y + 24)/5
Therefore, x = 4(y + 6)/5
1. Add -4.5 to 18.5
2. Divide 23 by 7
3. Then subtract 6 from -2.7
Answer:
8 16 24 32 <u>40</u> 48 56 64 <u>72</u>
1 2 3 4 <u>5</u> 6 7 8 <u>9</u>
Step-by-step explanation:
The proportion is 8:1
When the dollar amounts increase by 8, the hour amounts increase by 1, and vice versa. That is why it is a proportion.
Answer:
y=-2x+9
Step-by-step explanation:
Answer:
40
Step-by-step explanation:
Using the method of prime factors
8 = 2 × 2 × 2 = 2³
2 = 2
5 = 5
Then LCM = 2³ × 5 = 8 × 5 = 40